Mastering Autodesk Inventor : configured design - Cooper, Adam (InfiniteSkills, 2014)
"In this Inventor Configured Design training course, expert author Adam Cooper teaches you all about the key configurations in Autodesk Inventor. This course is designed for users that already have a working knowledge of Inventor. You will start by learning about iFeatures, including how to create and edit an iFeature, various application options, and copying Features vs. iFeatures. Adam will then teach you about creating iParts, including iPart documentation, updating, and content center publishing. This video tutorial will talk about iAssemblies, showing you how to create basic iAssemblies, multi-level iAssemblies, and how to document and update iAssemblies. Finally, you will learn about iLogic, rule options and wizards, and conditional statements."--Resource description page.